Isolation of the gene encoding the Hin recombinational enhancer binding protein. - Johnson, R C (1988)
In vitro DNA inversion mediated by the protein Hin requires the presence of a recombinational enhancer sequence located in cis relative to the recombination sites and a protein, Fis, which binds to the enhancer. We have cloned and determined the primary sequence of the gene encoding Fis. The deduced amino acid sequence of Fis indicates that the protein is 98 amino acids long and contains a potential helix-turn-helix DNA binding motif at its carboxyl terminus. The gene encoding Fis maps at 72 min on the Escherichia coli chromosome. The construction of mutant strains of E. coli that lack a functional fis gene demonstrates that Fis is not essential for cell growth under laboratory conditions but is required for high rates of Hin-mediated site-specific inversion in vivo.